Genotyping Squamous Cell Lung Carcinoma in Colombia (Geno1.1-CLICaP) - Cardona, Andrés F.; Ruiz-Patiño, Alejandro; Arrieta, Oscar; Ricaurte, Luisa; Zatarain-Barrón, Zyanya Lucia; Rodriguez, July; Avila, Jenny; Rojas, Leonardo; Recondo, Gonzalo; Barron, Feliciano; Archila, Pilar; Sotelo, Carolina; et al. (Frontiers in Oncology, 2020)
Background: Lung cancer is a public health problem, and squamous cell carcinoma (SCC) is the second most prevalent subtype of this neoplasm. Compared to other subtypes, including adenocarcinoma, SCC is less well understood in terms of molecular pathogenesis, limiting therapeutic options among targeted agents approved for other disease subgroups. In this study, we sought to characterize the SCC genomic profile using a validated Next Generation Sequencing (NGS) platform. Methods: The comprehensive NGS assay (TruSight Tumor 170) was used in order to target the full coding regions of 170 cancer-related genes on SCC samples. PD-L1 expression in tumor cells (TCs) was assessed using clone 22C3 (Dako). Clinical outcomes were correlated with molecular profile, including progression free survival (PFS), overall response rate (ORR), and overall survival (OS). Results: A total of 26 samples were included, median age was 67 years (r, 33-83) and 53.8% were men. Tobacco consumption was identified in all subjects (mean 34-year package). For first-line treatment 80.8% of patients received cisplatin or carboplatin plus gemcitabine. In terms of molecular profile, we identified a high prevalence of inactivating mutations in TP53 (61.5%), PIK3CA (34.6%), MLL2 (34.6%), KEAP1 (38.4%) and NOTCH1 (26.9%). PD-L1 expression ranged from negative, 1%, 2-49% and ≥50% in 23.1%, 38.5%, 26.9% and 11.5%, respectively. Interestingly, the genetic alterations did not have an effect in PFS, OS or ORR in this study. However, PDL1 expression was higher among those who had mutations in TP53 (p=0.037) and greater expression of PDL1 was related to PIK3CA alterations (p=0.05). Conclusions: The genomic profile of SCC encompasses important genes including TP53, PIK3CA and KEAP1. TP53 mutations could be associated with PDL1 expression, generating hypothesis regarding specific treatment options.